2020
DOI: 10.3390/molecules25235609
|View full text |Cite
|
Sign up to set email alerts
|

Production of Verbascoside, Isoverbascoside and Phenolic Acids in Callus, Suspension, and Bioreactor Cultures of Verbena officinalis and Biological Properties of Biomass Extracts

Abstract: Callus, suspension and bioreactor cultures of Verbena officinalis were established, and optimized for biomass growth and production of phenylpropanoid glycosides, phenolic acids, flavonoids and iridoids. All types of cultures were maintained on/in the Murashige and Skoog (MS) media with 1 mg/L BAP and 1 mg/L NAA. The inoculum sizes were optimized in callus and suspension cultures. Moreover, the growth of the culture in two different types of bioreactors—a balloon bioreactor (BB) and a stirred-tank bioreactor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
0
22
1
Order By: Relevance
“…The optimization of cultivation depends on the type of bioreactor used and its operation, including aeration and immersion time, which is widely reported in the literature [60,61]. This has been demonstrated by us for both Schisandra chinensis [62] and Verbena officinalis cultures [63]. It was shown that the operation conditions influenced the accumulation of flavonoids, phenolic acids, and phenylpropanoid glycosides.…”
Section: Metabolitementioning
confidence: 74%
“…The optimization of cultivation depends on the type of bioreactor used and its operation, including aeration and immersion time, which is widely reported in the literature [60,61]. This has been demonstrated by us for both Schisandra chinensis [62] and Verbena officinalis cultures [63]. It was shown that the operation conditions influenced the accumulation of flavonoids, phenolic acids, and phenylpropanoid glycosides.…”
Section: Metabolitementioning
confidence: 74%
“…Previously, we demonstrated the biotechnological possibilities of producing some phenylpropanoid glycosides and phenolic acids in the biomass of undifferentiating V. officinalis callus and suspension cultures that were maintained in Erlenmeyer flasks, as well as in special balloon and stirred-tank bioreactors. In these studies, we investigated the influence of different plant growth regulators (PGRs), light conditions, and inoculum size on biomass growth and metabolic profile [ 19 , 20 , 21 ]. The results showed that verbascoside was produced at an extremely high level, with a maximum amount of 9.18 g/100 g DW found in the suspension cultured in stirred-tank bioreactors [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, we investigated the influence of different plant growth regulators (PGRs), light conditions, and inoculum size on biomass growth and metabolic profile [ 19 , 20 , 21 ]. The results showed that verbascoside was produced at an extremely high level, with a maximum amount of 9.18 g/100 g DW found in the suspension cultured in stirred-tank bioreactors [ 20 ]. These results are plausible given the various biological properties of verbascoside, such as antioxidant, anti-inflammatory, cytoprotective, antibacterial, antiviral, and antiandrogen activities [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Verbena officinalis L. (V. officinalis), also known as common vervain, is a medicinal herb, widespread throughout the globe, mainly in the temperate climate zone (Kubica, Szopa et al, 2020b). In China, V. officinalis is widely distributed in the southern part of the Yellow River and has been used as traditional Chinese medicine for the treatment of rheumatism, bronchitis, depression, insomnia, anxiety, liver and gallbladder diseases (Khan, Khan et al, 2016, Kubica, Szopa et al, 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…In China, V. officinalis is widely distributed in the southern part of the Yellow River and has been used as traditional Chinese medicine for the treatment of rheumatism, bronchitis, depression, insomnia, anxiety, liver and gallbladder diseases (Khan, Khan et al, 2016, Kubica, Szopa et al, 2020a. Recent reports suggest that V. officinalis has a number of scientifically proven activities, such as antioxidant, antibacterial, antifungal, anti-inflammatory, analgesic, anticonvulsant, anxiolytic, antidepressant, sedative, hypnotic, wound healing, gastro-protective, anti-cancer and insecticidal properties (Casanova, Garcia-Mina et al, 2008, Kubica et al, 2020b, Lopez-Jornet, Camacho-Alonso et al, 2014, Speroni, Cervellati et al, 2007. In addition to being used as an antimicrobial, secretolytic, expectorant and diuretic agent, V. officinalis is also widely used in food and cosmetics, especially due to its antioxidant, antibacterial, and anti-inflammatory properties (Kubica et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%